2018
DOI: 10.1089/jwh.2016.6240
|View full text |Cite
|
Sign up to set email alerts
|

Women's Heart Health: Knowledge, Beliefs, and Practices of Canadian Physicians

Abstract: There is a clear need to educate physicians about heart disease in women and its prevention and management. More female-specific research, prevention, and clinical programs will enhance our ability to significantly improve cardiovascular health in Canadian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…A 2017 survey of interdisciplinary health care providers indicated that only 50%-60% were aware of the future CV health risks associated with common pregnancy complications. 9 This result was surprisingly similar to findings reported by Smith and colleagues 10 years earlier, in which approximately 50% of physicians reported referring women after HDP for follow-up care. 10 However, other studies have shown that only 20% of women reported having been counselled on their risks of future CVD.…”
Section: Current State and Gaps In Postpartum CV Preventive Care In Canadasupporting
confidence: 89%
See 2 more Smart Citations
“…A 2017 survey of interdisciplinary health care providers indicated that only 50%-60% were aware of the future CV health risks associated with common pregnancy complications. 9 This result was surprisingly similar to findings reported by Smith and colleagues 10 years earlier, in which approximately 50% of physicians reported referring women after HDP for follow-up care. 10 However, other studies have shown that only 20% of women reported having been counselled on their risks of future CVD.…”
Section: Current State and Gaps In Postpartum CV Preventive Care In Canadasupporting
confidence: 89%
“…Furthermore, many Canadian health care providers were not aware of the existence of these pregnancy-related guidelines. 9 Thus, general awareness among front-line physicians could be improved if recommendations were consolidated in a single document summarizing the highest quality evidence for CV risk factor screening, prevention, and treatment after pregnancy complications.…”
Section: Current State and Gaps In Postpartum CV Preventive Care In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…1 Moreover, a lack of awareness among health care professionals was revealed in a 2018 survey of a random sample of 504 Canadian primary care physicians (38%) and cardiologists (32%) who indicated that more men than women die of CVD when in fact, the numbers are approximately equal with CVD being a major cause of death in both sexes. 2 Although there was previous optimism in the United States as public awareness of CVD as a leading cause of death for women increased by an absolute 26% (from 30% to 56%) between 1997 and 2012, 3 unfortunately, the most recently published iteration of the American Heart Association survey concluded that this awareness declined from 2009 to 2019 in all races/ethnicities and ages, except in women older than 65 years. 4 The greatest declines in awareness were among Hispanic (14% decline) and non-Hispanic black (31% decline) women, and in younger women (aged 25-34 years; 19% decline), in whom primordial/primary prevention might be most effective.…”
Section: R Esum Ementioning
confidence: 99%
“…Physicians have oft-described persistent barriers to the adoption and institutionalization of preventive treatment, education and counseling practices in clinic - described in detail elsewhere, these include lack of time, pressures to handle more pressing issues, lack of resources and perceptions of lack of (convenient) evidence-informed materials, lack of reimbursement or financial incentives, low expectations of benefit, concern about offending patients (e.g. suggesting weight loss), lack of confidence in outcome benefits, and low self-efficacy (confidence in delivering preventive/lifestyle care) [88].…”
Section: Barriers To Change - Authoritarianism Social Dominancementioning
confidence: 99%